THE ANALYSIS OF FACTORS THAT INFLUENCE DIVIDEND POLICY IN MANUFACTURING COMPANIES PERIOD 2013 - 2016 REGISTERED IN INDONESIA STOCK EXCHANGE - Nasution, Yusneni Afrita (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to examine and analyze the factors thatinfluence Dividend Policy in manufacture companies period 2013 – 2016 listed in Indonesia Stock Exchange. The research used associative research method. The population was 144 manufacture companies listed in BEI in the period of 2013-2016, and 26 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using panel regression analysis using Eviews 10 software. The result of the research showed that the variables of profitability, credit policy, firm growth, liquidity and firm size simultaneously had influence on dividend policy. Partially, profitability (ROE) had positive and significant influence on dividend policy, credit policy (DER) had negative and significant influence on dividend policy, firm growth (TAG) had negative but insignificant influence on dividend policy, liquidity (CR) had negative but insignificant influence on dividend policy, and firm size (SIZE) had positive and significant influence on dividend policy.